ANALISIS YURIDIS TERHADAP PENITIPAN SERTIPIKAT KEPADA NOTARIS/PPAT TERKAIT PROSES PERALIHAN HAK ATAS TANAH (STUDI PUTUSAN PENGADILAN NEGERI NOMOR 53/PID.B/2017/PN.BKT) - DARA TRIANI PUTRI (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Dr. Suprayitno, SH, MKn2. Dr. Henry Sinaga, SH, MKn3. Dr. T. Keizerina Devi A, SH, CN, MHum The procedures of depositing land title certificates to a Notary/Land Title Registrar (hereinafter is referred to as PPAT) have not yet been explicitly and obviously regulated in term of the authority/obligations and prohibition for the Notary/PPAT to accept the deposit related to land title transfer. However practically, the certificate deposit is frequently performed by Notary/PPAT for the land title transfer process. Consequently, Notary/PPAT can be accused for embezzlement, for example, the district court ruling No. 53/Pid.B/2017/PN.BKT. The results of the research conclude that it is actually compulsory to deposit certificates to Notary/PPAT related to land title transfer process because PPAT shall firstly verify the land title to the National Land Office by matching the land title certificate in the lists of certified land in the local Land Office, and PPAT needs to show the original certificate as stipulated in the Regulations of Ministry of Agrarian/Head of National Land Office. Notary/PPAT cannot be held criminal accountable because there are buyer’s rights that have to be protected in the sale and purchase contract deed that he makes. When the certificate is deposited, Notary/PPAT makes a receipt acknowledgement letter for all parties. however, the Notary/PPAT have to be truthful in transferring the land title, because they can be held accountable administratively or civilly and there are sellers that feel being financially harmed by the legal action of Notary/PPAT.Keywords: Certificate Deposit, Notary/PPAT, Embezzlement